2009
DOI: 10.1093/jnci/djp046
|View full text |Cite
|
Sign up to set email alerts
|

Cause-Specific Mortality in Long-Term Survivors of Retinoblastoma

Abstract: The temporal patterns of site-specific excess risks of subsequent malignant neoplasms in retinoblastoma survivors should inform screening programs designed for the early detection and treatment of subsequent malignant neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 29 publications
3
100
0
3
Order By: Relevance
“…Survivors of non-hereditary Rb are at much lower risk of a subsequent primary cancer, similar to the risk in the general population [8]. The risk for sarcomas in hereditary patients has been attributed to genetic susceptibility and past treatment with radiation [9].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Survivors of non-hereditary Rb are at much lower risk of a subsequent primary cancer, similar to the risk in the general population [8]. The risk for sarcomas in hereditary patients has been attributed to genetic susceptibility and past treatment with radiation [9].…”
Section: Resultsmentioning
confidence: 90%
“…The majority of bone sarcomas occurred within the radiation field in the head region, but up to 40% was diagnosed outside the treatment field, primarily in the lower legs [9].…”
Section: Resultsmentioning
confidence: 99%
“…In our data example, further composite endpoints were disease-free survival and overall survival. Also overall survival can be regarded as composite, because one can distinguish between cancer-related mortality and noncancer mortality (27,28). If the composite time-to-event endpoint is all-encompassing in the sense that every patient will at some point in time experience it (although potentially after study closure), standard survival analyses using Kaplan-Meier curves and Cox' regression analyses for the all-events hazard are adequate.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of secondary malignancies in germinal retinoblastoma survivors has been the topic of study in many reports, (Abramson et al, 2001;Eng et al, 1993;Fletcher et al, 2004;Kleinerman et al, 2005;MacCarthy et al, 2009;Marees et al, 2008;Moll et al, 1997;Wong et al, 1997;& Yu et al, 2009) but the variance of sample size and study design in these reports has made interpretation of the cumulative incidence difficult. Using reported cumulative risk rates from sizeable studies with appreciable longterm follow-up, incidence rates are approximately 0.5% to 1% per year.…”
Section: Epidemiologymentioning
confidence: 99%
“…Historically, male retinoblastoma survivors were reported to have a higher incidence of third malignancies, primarily because females had an increased overall mortality rate from second malignancies (Abramson et al, 2001;Eng et al, 1993). More recent studies, however, have no longer identified an increase in female mortality from second malignancies (Marees et al, 2009;Yu et al, 2009). Abramson et al (Abramson et al, 2001) reported a predictable pattern for third, fourth, and fifth malignancy development based on location of the second tumor.…”
Section: Malignantmentioning
confidence: 99%